HIBAH KEPADA ANAK LI’AN DALAM PERSPEKTIF HUKUM ISLAM - IKA AMALIA SYAFITRY LUBIS (PREMISE LAW JURNAL, 2016)
Principally, li’an separates mula’anah (cursing to each other) husband and wife. When a husband accuses his wife of committing adultery, he presents four witnesses, and he swears an oath four times, saying that he is right. In his fifth oath, he says that he will be cursed by Allah if his accusation is false. The wife, who objects the accusation, then takes an oath four times and says that she will be cursed by Allah if her husband’s accusation is found to be true. If a man denies his child and his denial is in line with his li’an, the relationship between him and his child is annulled, and there is no obligation to support the child financially. The effect of li’an is great; a li’an child absolutely does not get any compensation in his father’s property; therefore, hibah (grant) is the only good way to be given to a li’an child. Kata kunci : Hibah, Li’an, Islamic law